2019
DOI: 10.18632/oncotarget.26714
|View full text |Cite
|
Sign up to set email alerts
|

Aurora A inhibition limits centrosome clustering and promotes mitotic catastrophe in cells with supernumerary centrosomes

Abstract: The presence of supernumerary centrosomes is prevalent in cancer, where they promote the formation of transient multipolar mitotic spindles. Active clustering of supernumerary centrosomes enables the formation of a functional bipolar spindle that is competent to complete a bipolar division. Disruption of spindle pole clustering in cancer cells promotes multipolar division and generation of non-proliferative daughter cells with compromised viability. Hence molecular pathways required for spindle pole clustering… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 56 publications
3
18
0
Order By: Relevance
“…HSET overexpression is prominent in many cancer contexts where its expression corresponds with increased cell proliferation (90,91). This relationship with proliferation is independent of centrosome number, though in cancer contexts where centrosome number is amplified, HSET is additionally required to cluster extra spindle poles into a bipolar spindle (78,(92)(93)(94)(95)(96). We have confirmed that our model captures spindle-pole collapse in the context of high HSET activity (Fig.…”
Section: Cortical Dynein Is Required For Spindle Bipolarity When Hset Activity Is Highsupporting
confidence: 76%
See 2 more Smart Citations
“…HSET overexpression is prominent in many cancer contexts where its expression corresponds with increased cell proliferation (90,91). This relationship with proliferation is independent of centrosome number, though in cancer contexts where centrosome number is amplified, HSET is additionally required to cluster extra spindle poles into a bipolar spindle (78,(92)(93)(94)(95)(96). We have confirmed that our model captures spindle-pole collapse in the context of high HSET activity (Fig.…”
Section: Cortical Dynein Is Required For Spindle Bipolarity When Hset Activity Is Highsupporting
confidence: 76%
“…We propose that dynamic changes in bipolar spindle length, driven by cortical dynein activity, contributes to the spindle length requirements for chromosome capture and alignment, with particular relevance to cancer contexts where chromosome number is increased. In cancer contexts where supernumerary centrosome are present, HSET-dependent centrosome clustering promotes bipolar spindle formation [75,76,77,78,66,79]. High HSET levels have also been reported in cancer cells independent of centrosome number, although the functional implications of high HSET activity in this context remains unclear [73,74].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, KIFC1 [6668] and TACC3 [69,70] are also required for acentrosomal spindle assembly in multiple organisms, suggesting that cancer cells may be dependent on these meiotic mechanisms to form bipolar spindles when the centrosome complement of the cell is abnormal. Aurora-A is also required for clustering [32]. This is particularly noteworthy as Aurora-A is a mitotic kinase required for both TACC3 spindle localisation [71,72] and HURP activity [31].…”
Section: Proteins Required For Centrosome Clusteringmentioning
confidence: 99%
“…Although centrosome amplification is a common characteristic of solid and hematological cancers, cancer cells tend to cluster supernumerary centrosomes into two group to enable a bipolar mitosis [Kwon et al ]. Recently, it has shown that Aurora‐A inhibition limits centrosome clustering and promotes mitotic multipolarity in cells with supernumerary centrosomes [Navarro‐Serer et al ]. With these in mind, it is therefore tempting to speculate that multipolar spindle and multinucleation induced by geraniin in HCT116 cells may be the combined consequences of centrosome overduplication and declustering resulting from reduced expression of Plk‐4 , Plk‐1 , and Aurora‐A .…”
Section: Disscussionmentioning
confidence: 99%